Reverz / Haris Danial Yusri - Yusri, Haris Danial (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Reverz is a reversible bucket hat. The design and colour can be change by just a flip. I choose a chameleon as the product's icon because chameleon reflects the same personality as the product. Reverz is the abbreviation for reversible. The product description is "Reversible Bucket Hat". The product tagline is "Flip Your Style", which means the different design can reflects different personality. The unique selling point {USP) is a reversible bucket hat, which could switch personality and style in a single flip. The client of this product is Hornbill Time and Wear, which is known in creating timeless fashion items such as watch, bucket hat and socks. This timeless that inspired though our love to Malaysian art, culture and heritage. One of the products I chose for my final year project is the bucket hat because their bucket hat is one of my favorite items from them. Product concept is fun, funky look and unique. The reason I chose this concept is to specifically targeted to young generation which is more up-to-date with the current trend and lifestyle.The design that used for the product are bright colors such as bright yellow, turquoise, purple and blue. It also features a lot abstract design for the brand itself in the packaging to make it more interesting and eye-catching. I chose this concept since practically every reversible bucket hat I see in stores has a design that is more common. This concept, I believe, has the potential to draw the attention of the community as well as bucket hat lovers. For my product market there are many international competitor for example Nike, Adidas, New era and pretty green. For local product is Pestle mortar clothing, Super Sunday, TNT.CO, and many more. Reverz hopes to be a fashionable item among the youngsters as it is the current trend and lifestyle. As the product designer, I am really satisfied with its overall appearance and feel. I believe that Reverz will surpass other well-known brands in Malaysia and will become a great competitor to others brand.